Estimates of genetic and phenotypic parameters for first lactation and lifetime performance traits in Hariana cattle - DALAL, D S; RATHI, S S; RAHEJA, K L (The Indian Journal of Animal Sciences, 2014)
Data on 601 Hariana cows maintained at Government Livestock Farm, Hisar, during 1976-96 were used to estimate heritabilities, genetic and phenotypic correlations between first lactation and lifetime performance traits. Model used for estimation of sire and residual variance and covariance components included year-season of calving and sire genetic group as fixed effects and sire within sire genetic group as random effect. The averages for age at first calving (AFC), first lactation milk yield (FLMY), first lactation length (FLL), peak yield (FPY), first service period (FSP), first dry period (FDP) and first calving interval (FCI) were 1 443 ± 7.26 days, 1 081 ± 14.21 kg, 268 ± 2.15 days, 6.16 ± 0.06 kg, 192 ± 3.77 days, 210 ± 3.36 days, and 479 ± 3.88 days respectively. Herd life (HL), lifetime milk yield (LTMY), productive life (PL), no. of days in milk (ND) and milk yield per day of productive life (MY IPL) were 1 719 ± 29.80 days, 5 304 ± 118 kg, 1 629 ± 26.99 days, 1 033 ± 18.91 days and 3.10 ± 0.04 kg respectively. Heritability estimates for AFC, FLMY, FLL. PY, FSP, FDP and FCI were 0.38 ± 0.18, 0.11 ± 0.09, 0.22 ± 0.15, 0.10 ± 0.08, 0. 18 ± 0.11, 0.14 ± 0. 10 and 0.21 ± 0.11 respectively. Heritabilities for lifetime performance traits were lower than heritability estimates of first lactation traits. AFC had high negative genetic correlation with FLMY and PY. However, genetic correlation of AFC with FLL. FSP. FDP and FCI were high and positive. FLMY and PY had high positive genetic correlations with lifetime traits. The corresponding phenotypic correlations were also significant and positive. Results suggested that selection on the basis of AFC and FLMY would be expected to increase lifetime milk performance traits.